Selected issues in hospitality and tourism sustainability - Hassan, Hamimah (Universiti Putra Malaysia Press, 2014)
This book focuses on research work undertaken in Hospitality and Tourism areas. The titles were selected from papers that were reviewed and accepted for this book publication, hence providing a platform for researchers including the post-graduate students to showcase their research work and exchange research ideas. It is also our objective to highlight issues in tourism and hospitality in relations to sustainability, tourism product development and marketing strategies. As such, the book has 10 chapters that cover wide ranges of Hospitality and Tourism issues faced by organizations as well as policy makers. We wish to thank all the contributors for their paper(s) and Faculty of Economics and Management of University Putra Malaysia (UPM) for funding the project. In particular, our appreciation is extended to the Dean of Faculty of Economics and Management, University Putra Malaysia, Prof. Dr. Mohd. Shahwahid Othman, Prof. Madya Dr. Yuhanis Abdul Aziz, Head of Marketing and Management Department and our external examiners for their supports in making this book a reality.